CD4 Association with Mortality in HIV Patients with Dyspnea in Dr Seotomo General Academic Hospital Surabaya - Moh. Hamzah Raka Pratama; Muhammad Vitanata Arfijanto; Maria Lucia Inge Lusida (Universitas Airlangga, 2023)
Introduction: HIV AIDS patients who have a CD4 count < 200 cells/uL often complain of respiratory symptoms (Wallace, 1993). The complaint was shortness of breath (62%). Opportunistic infections (IO) in HIV patients are also brought on by a decreased CD4 count of 200 cells/uL (Peters, 2007). HIV/AIDS patients with CD4 < 200 cells/uL have a risk of death of 10.399 (Kusumaadhi, 2021). This study aims to determine the association between CD4 cell count with mortality in HIV patients with shortness of breath at Cendana, Dr. Soetomo General Academic Hospital Surabaya, during the period of January–December 2020.Methods: This study used a cross-sectional retrospective design. The population in this study were patients diagnosed with HIV at Cendana, Dr. Soetomo General Academic Hospital, using a total sampling technique. The variables studied were the CD4 counts as the independent variable, and the mortality of HIV patients with dyspnea as the dependent variable. The sample in this study must meet the inclusion criteria, namely, the sample must have a history of CD4 counts in their medical record in the last 2 to 3 months while in Cendana, Dr. Soetomo General Academic Hospital. Secondary data from medical record data in Cendana, Dr. Soetomo General Academic Hospital, was used for the research from January to December 2020. Results: A total of 128 HIV patients with dyspnea and a history of CD4 counts in the previous 3 to 4 months were included in the study: 79 (61.7%) males and 49 (38.3%) females. The most common age groups were 31–40 years (33.6%), 20–30 years (32.0%), 41–50 years (23.4%), and > 60 years (2.4%), with no patients under the age of 20. The distribution of the most opportunistic infections were: pneumocystis pneumonia (n = 62), tuberculosis (n = 49), and bacterial pneumonia (n = 17). Patients lived (n = 79) and died (n = 49) in total.Conclusion: There was no significant association between CD4 count and mortality in HIV patients with dyspnea (p-value 0.084 > 0.05).